Basic Principles of The Study of The Integration Of Islam, Science and Indonesian Culture - Alkhonsa Mardhiyya; Moh Roqib; Kurniawan Azzaky (Transformasi Manageria: Journal of Islamic Education Management, 2024)
This research aims to theoretically explain the basic principles of the Integration of Islam, Science and Indonesian Culture. The method used in this research is Library Research. The results of this research are that the integration that occurs between Islam, Science and Indonesian Culture is confirmed where religion is the basis of faith in carrying out science and culture. Faith also exists in science which believes that the universe has orderly and rational laws, and culture which takes place on the basis of belief in an entity that has the power behind its implementation is faith, so it can be understood that monotheism is the basic principle of the integration of Islam, Science and Indonesian Culture. As we understand, tawhid itself is the faith or aqidah that identifies a Muslim, resulting in the development of Islamic civilization throughout the world.